2017
DOI: 10.1177/1045389x17730909
|View full text |Cite
|
Sign up to set email alerts
|

Performance tests and modeling on high damping magnetorheological elastomers based on bromobutyl rubber

Abstract: A new kind of magnetorheological elastomer with the matrix of the bromobutyl rubber is developed. The magnetoviscoelasticity properties of the magnetorheological elastomer specimens are investigated with respect to different magnetic fields, displacement amplitudes, and frequencies under sinusoidal loadings. The experimental results show that the shear storage modulus and the loss factor of magnetorheological elastomers increase with the increasing magnetic field, excitation frequency, and the weight fraction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…The compressive toughness, deformation and energy dissipation capacity of PVA-steel HyFRCC can be significantly improved. It is indicated that PVA-steel HyFRCC can be used for vibration isolation and mitigation of structures to improve the seismic performance of structures (Kasai et al, 1998;Xu et al, 2017Xu et al, , 2019.…”
Section: Resultsmentioning
confidence: 99%
“…The compressive toughness, deformation and energy dissipation capacity of PVA-steel HyFRCC can be significantly improved. It is indicated that PVA-steel HyFRCC can be used for vibration isolation and mitigation of structures to improve the seismic performance of structures (Kasai et al, 1998;Xu et al, 2017Xu et al, , 2019.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the abovementioned elastomer matrices, some other popular materials are utilized in actual applications, for example, isobutylene-isoprene rubber [36] , bromobutyl rubber [37] , and mixed matrices [38][39][40] . Zhang et al [38] admixed cis-polybutadiene rubber and natural rubber.…”
Section: Elastomer Matricesmentioning
confidence: 99%
“…Additionally, the properties of the aligned MRE composites filled with nanowires synthesized from typical ferromagnetic metals (Fe, Co, and Ni) were investigated. Zhu et al (2012Zhu et al ( , 2013 and Xu et al (2018a) investigated the magnetoviscoelasticity properties of the MREs in the condition of different magnetic fields, displacement amplitudes, and frequencies under sinusoidal loadings, then proposed a parameter model to describe MREs performances.…”
Section: Smart Vibration Mitigation Materialsmentioning
confidence: 99%